Building cultural competence : innovative activities and models - Berardo, Kate; Deardorff, Darla K. (Stylus Publishing LLC, 2012)
"Building Cultural Competence presents the latest work in the intercultural field and provides step-by-step instructions for how to effectively work with the new models, frameworks, and exercises for building learners' cultural competence. Featuring fresh activities and tools from experienced coaches, trainers, and facilitators from around the globe, this collection of over 50 easy-to-use activities and models has been used successfully worldwide in settings that range from Fortune 500 corporations to the World Bank, non-profits, and universities."--Publisher's description